O uso de dobraduras no ensino de geometria na educação básica: desafios e possibilidades - Matos, Thaís Menandra Santos dos Anjos de (2025)
This study aims to investigate the teaching of geometric solids through the folding technique, focusing on its application in Basic Education. The methodological proposal is grounded in the principles of Euclidean Geometry and the didactic possibilities offered by the use of origami as a pedagogical resource. The research was conducted within the scope of Basic Education, through the implementation of practical activities with high school students, seeking to understand the extent to which the use of paper folding can contribute to the comprehension of concepts such as vertices, edges, faces, nets, surface area, and volume of solids. The qualitative analysis of the data revealed that the approach using paper folding fosters more concrete, dynamic, and meaningful learning, as well as stimulating students’ spatial visualization and geometric reasoning. The theoretical foundation included authors such as Fiorentini (2006), Lorenzato (2009), Lira (2015), among others, in addition to the application of the Huzita-Hatori axioms to mathematically justify the constructions made with paper. The study concludes that the use of paper folding proves to be an effective strategy for the recovery of learning in Geometry, presenting both challenges and possibilities that help make teaching more accessible and attractive to students. It is concluded that origami is an effective, accessible, and BNCC-aligned pedagogical strategy, capable of significantly contributing to the recovery of Geometry learning.